Analisis keuntungan dan resiko investasi Cryptocurrency untuk pemula - M. Frisky Pandu; Febryantahanuji Febryantahanuji (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze cryptocurrency investments and the risks faced by beginner investors who own digital assets such as Bitcoin, Solana, XRP, and other coins that have been increasing in value over the past few years, especially among the general public and retail investors. Not only retail investors, but governments also now hold digital assets, as has already happened. However, the unstable price and lack of global legal oversight make investing in cryptocurrency highly risky, especially for those with less knowledge and experience. The methods used in this study include literature review, descriptive analysis of historical price data for cryptocurrency, case studies, and interviews with several beginner investors. The findings show that cryptocurrency can generate large profits in a short time, but the risk of losing capital is also very high. Therefore, having a good understanding of blockchain technology, risk management, and investment psychology before starting to invest is important. This study is hoped to serve as a reference for beginner investors when considering decisions to invest in cryptocurrency.